Building and managing e-book collections : a how-to-do-it manual for librarians - Kaplan, Richard, 1954- (London : Facet Pub., 2012)
This book provides an overview and analysis of current and emerging trends of the use and development of the e-book. Readers will learn best practices to guide them in developing library policies and procedures involving the acquisition, purchase, collection development, cataloguing and retention of e-books.
Includes bibliographical references and index.
Keywords: Digital libraries -- Collection development